Predicting sexual diversity based on Islamic mental health - Gholamibarzaki, Marziyeh; Abolmaali, Khadije; Moumivand, Majid (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study was to predict sexual diversity based on Islamic mental health. The method of the present study was descriptive-correlation. The statistical population included married men and women studying at the Islamic Azad University - Roodehen in 2014. The sample was selected by cluster random sampling. 200 participants completed two questionnaires on Islamic mental health and sexual diversity. Simple regression test was used to analyze the data. Findings showed that Islamic mental health negatively predicted the overall score of sexual desire and its behavioral dimension, the other two components of sexual diversity (moral orientation and reinforcement), did not predict based on Islamic mental health.Given that the findings of the present study indicate that Islamic mental health has predicted sexual diversity, psychiatrists in the treatment of sexual diversity in the treatment of sexual (religious) -religious-spiritual-faith dimension of therapists. Given that the findings of the present study indicate that Islamic mental health has predicted sexual diversity, psychiatrists in the treatment of sexual diversity in the treatment of sexual (religious) -religious-spiritual-faith dimension of therapists.